Situational analyses on cowpea value chain in Zambia: the case of an untapped legume - Mwila, N.M.; Munyinda, K.; Mwala, M.; Kamfwa, K.; Kambikambi, T.; Siyunda, A.; Sinyangwe, S.; Kanenga, K.; Alamu, Emmanuel Oladeji; Rubaihayo, P. (Informa UK Limited, 2022)
Cowpea (Vigna unguiculata (L.) Walp) is a vital legume crop for Zambia’s urban and rural households. The crop is an important legume used as human and animal food and as a component of the agricultural production system, which improves the fertility of many depleted soils because of its ability to fix atmospheric nitrogen. Government through the ministries of health and agriculture recommend its’ use. Despite the importance of cowpea in the nation, there is limited information on the crop along with its’ value chain components. This review aims to assemble pertinent information on cowpea and its value chain components in Zambia. A critical look through the food system from production to consumption reveals the prevailing gaps in knowledge and output. The information covered here touches on crop breeding, production, marketing, processing, and consumption. This paper delves into various literature, bringing out the salient issues that are not commonly discussed about on the crop. It is a situation analyses focusing on finding solutions to improving the relevance and appreciation of the crop. There is a need for agricultural policies to promote cowpea production and use with the active participation of relevant actors. This would create a conducive environment for determining user needs, and leading to the development of beneficial impact-related activities at various stages. The country needs to begin incorporating a variety of crops within the food system to complement maize to improve nutrient intake, contribute to climate-smart practices, and sustainability of agricultural practices within communities in Zambia.